Exploring the connection between children's literature and music - Carlow, Regina (Westport, Conn. : Libraries Unlimited, 2008)
From the Publisher: This author provides the shoulder for children's librarians, preschool providers, and preschool teachers to lean on to share music with the children in their programs. They will find everything they need to know to be comfortable when they are planning musical activities with their stories
1: Introduction -- 2: Rationale for singing with young children -- 3: Other ways to be musical -- 4: Working with preschool children -- 5: Primary grades: K-2 -- 6: Working with the intermediate grades: 3-5 -- 7: Some final thoughts -- Appendix A: Glossary of musical terms -- Appendix B: Tunes used in lesson ideas in chapters 4-6 -- Appendix C: Musical works -- Appendix D: Bibliography -- Index
Includes bibliographical references (pages [119]-121) and index
Keywords: School music -- Instruction and study -- Activity programs; Children's poetry -- Study and teaching -- Activity programs; Early childhood education